2019
DOI: 10.1111/ecog.04194
|View full text |Cite
|
Sign up to set email alerts
|

Zoogeographical regions and geospatial patterns of phylogenetic diversity and endemism of New World bats

Abstract: The analysis of regional scale patterns of diversity allows insights into the processes that have shaped modern biodiversity at the macro‐scale. Previous analyses studying biogeographic regionalisation across different high‐level taxa have shown similar trends at a global scale. However, incorporating phylogenetic methods when comparing biogeographic regionalisation between subgroups facilitates identification of mechanisms leading to the biogeographic distribution of specific taxa. We analysed the spatial tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
(185 reference statements)
0
8
0
Order By: Relevance
“…It is currently classified into 10 distinct ecoregions (biogeographical zones) (Olson et al, 2001), which were delimited concerning both resident taxa and geo-climatic data. Because species respond to environmental and spatial gradients, the ecoregions should present a correlation between beta diversity components, and geographical and environmental factors (Dos Anjos et al, 2018;López-Aguirre et al, 2019;Stevens, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently classified into 10 distinct ecoregions (biogeographical zones) (Olson et al, 2001), which were delimited concerning both resident taxa and geo-climatic data. Because species respond to environmental and spatial gradients, the ecoregions should present a correlation between beta diversity components, and geographical and environmental factors (Dos Anjos et al, 2018;López-Aguirre et al, 2019;Stevens, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for this controversy could be the analysis scale. For instance, studies that looked at bat diversity in a larger scale, such as the neotropical region, showed that spatial pattern was the most influential factor for explaining differences in bat diversity (López-Aguirre, Suzanne, Laffan, & Archer, 2019;Varzinczak et al, 2018). On the other hand, smaller-scale studies, covering a single biome, demonstrated that climate was the most influential factor for explaining bat species diversity (López-González et al, 2015;Stevens, 2013;Stevens et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To quantify geographical distribution patterns, species-level range maps were retrieved from the IUCN data repository and projected into an equal-area Mollweide projection. IUCN range maps were used as they have been shown to accurately capture macroecological patterns, similar to those found using other estimates of species' distributions (López-Aguirre et al, 2019). Distribution maps were then transformed into presence/absence records, after intersecting all 108 range maps with a grid of 100 × 100 km cells, producing a final presence/absence matrix for 108 species and 1678 cells.…”
Section: Species-level Datamentioning
confidence: 99%
“…If processes and conditions of dispersal are reduced because an archipelago such as the Hawaiian Islands is located far distant from mainland areas and other archipelagos, then the evolution of new taxa can help to optimize the nutrient cycling and resource use. As a result, the total number of taxa (S) on isolated islands often is relatively small compared with mainland areas of the same range size and similar ecological conditions, the number of endemics (E) is high, and the level of endemism (E/S) is extremely high [164][165][166].…”
Section: How Is Endemism Related To Continuity Change In Time and Iso...mentioning
confidence: 99%